Ultraviolet and Near‐Infrared Dual‐Band Selective‐Harvesting Transparent Luminescent Solar Concentrators. Issue 12 (4th February 2021) - Yang, Chenchen; Sheng, Wei; Moemeni, Mehdi; Bates, Matthew; Herrera, Christopher K.; Borhan, Babak; Lunt, Richard R.
Abstract: Visibly transparent luminescent solar concentrators (TLSC) can optimize both power production and visible transparency by selectively harvesting the invisible portion of the solar spectrum. Since the primary applications of TLSCs include building envelopes, greenhouses, automobiles, signage, and mobile electronics, maintaining aesthetics and functionalities is as important as achieving high power conversion efficiencies (PCEs) in practical deployment. In this work, massive‐downshifting phosphorescent nanoclusters and fluorescent organic molecules are combined into a TLSC system as ultraviolet (UV) and near‐infrared (NIR) selective‐harvesting luminophores, respectively, demonstrating UV and NIR dual‐band selective‐harvesting TLSCs with PCE over 3%, average visible transmittance (AVT) exceeding 75% and color metrics suitable for the window industry. With distinct wavelength‐selectivity and effective utilization of the invisible portion of the solar spectrum, this work reports the highest light utilization efficiency (PCE × AVT) of 2.6 for a TLSC system, the highest PCE of any transparent photovoltaic (TPV) devices with AVT greater than 70%, and outperforms the practical limit for non‐wavelength‐selective TPV. Abstract : Transparent luminescent solar concentrators (TLSC) incorporating massive‐downshifting phosphorescent nanoclusters and fluorescent organic molecules as ultraviolet and near‐infrared (NIR) selective‐harvesting luminophores, respectively, to maximize harvesting of the invisible solar spectrum are reported. The photoluminescence of both luminophores is tuned into the NIR to minimize visual impact. The dual‐band TLSCs show efficiencies over 3% with excellent visible transparency and color metrics.